Patagonia: where does it come from? - Ramos, Víctor A.; Naipauer, Maximiliano (Journal of Iberian Geology, 2014)
Based on the recent finding of archeocyathids in molassic middle Cambrian to Early Ordovician age-sequences of northern Patagonia the relationships between this southern part of South America and East Antarctica need to be re-examined. The early Cambrian age of the archeocyathids, and their derivation from the Shackleton Limestones, open several alternatives that are evaluated based on the lithology and the U-Pb zircon ages of the different metamorphic sequences of Patagonia and the Transantarctic Mountains. Based on these data, it is proposed that the Somuncurá Massif of northern Patagonia is the conjugate margin of the Pensacola Mountains in East Antarctica. The main episodes of deformation within the Cambrian-Ordovician Ross Orogeny are correlated, as well as the passive margin setting during the Silurian-Devonian, which indicate that the lower section of the Beacon Supergroup of Antarctica corresponds to the Sierra Grande Formation in Patagonia. These facts show that the Patagonian terrane may have been situated as the conjugate margin of the Transantarctic Mountains from Southern Victoria Land to the Pensacola Mountains. The rifting of Patagonia from Antarctica and the beginning of subduction along western Patagonia, are correlated among different terranes, showing a robust coherent evolution through early Paleozoic times among these blocks. The final amalgamation of Patagonia with Western Gondwana occurred in late Paleozoic times, but is not analyzed in the present contribution.